Transforming Insurance Risk Management through Advanced Data Analytics - Rakesh Maltumkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of advanced data analytics on insurance risk management. The article examines how modern analytical approaches, including machine learning, natural language processing, and predictive modeling, are revolutionizing traditional insurance operations. The article investigates various technical implementations across fraud detection, claims processing, customer segmentation, and risk assessment. The article covers data integration challenges, real-time processing architectures, and scalability solutions while exploring the business impact of these technological advancements. The article also discusses emerging technologies and future developments in the insurance sector, including advanced AI integration, IoT applications, and smart infrastructure implementation, providing insights into how these innovations are reshaping the insurance industry's approach to risk management and customer service.
Keywords: Advanced Analytics; Insurance Risk Management; Machine Learning Algorithms; Natural Language Processing; Predictive Modeling